Optimalisasi Pemanfaatan Sampah Bernilai Ekonomis dalam Mendukung Sustainable Development Goals (SDGs) di Kota Medan melalui Kegiatan Daur Ulang - Zainarti Zainarti; Zafira Alya Kirana (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
Waste management has become a critical issue in achieving sustainable development, particularly in urban areas such as Medan City, where the volume of waste continues to increase each year. This study aims to analyze the optimization of economically valuable waste utilization through recycling activities to support the Sustainable Development Goals (SDGs), using a literature-based approach. The method employed is a literature review by collecting, examining, and comparing previous research from national and international journals related to recycling practices, circular economy principles, and urban waste management. The findings indicate that the utilization of economically valuable waste—such as plastic, paper, metal, and organic materials—can generate economic benefits for communities while improving overall waste management efficiency. The reviewed studies also highlight several key factors influencing recycling success, including government policies, the availability of recycling facilities, public awareness, and collaboration with recycling industries. Optimizing waste utilization has been shown to contribute significantly to various SDGs targets, including waste reduction, improved community welfare, and environmental protection. Therefore, strengthening the recycling ecosystem through multi-stakeholder collaboration is essential for Medan City in promoting sustainable urban development.